Isolation and sequence analysis of Culex flavivirus from Culex interrogator and Culex quinquefasciatus in the Yucatan Peninsula of Mexico - Saiyasombat, Rungrat (2010)
Previously, we reported a high prevalence of Culex flavivirus (CxFV) in Culex quinquefasciatus (Say) in the Yucatan Peninsula of Mexico. To determine whether other Culex spp. mosquitoes in this region are susceptible to natural CxFV infection, Cx. bahamensis (Dyar and Knab), Cx. coronator (Dyar and Knab), Cx. interrogator (Dyar and Knab), Cx. nigripalpus (Theobald) and Cx. opisthopus (Komp) in the Yucatan Peninsula of Mexico were tested for CxFV. Two pools of Cx. interrogator were positive. The envelope protein genes of these isolates and 16 isolates from Cx. quinquefasciatus were sequenced and shown to have ≥99.2% nucleotide identity. These data suggest that there is limited genetic diversity among CxFV isolates in the Yucatan Peninsula of Mexico.